1990
DOI: 10.1061/(asce)0733-9445(1990)116:9(2361)
|View full text |Cite
|
Sign up to set email alerts
|

Live‐Load Moments for Continuous Skew Bridges

Abstract: Most of the study carried out in the field of skew bridges is of theoretical nature and does not provide any direct help to engineers designing bridges specially, for Indian loading conditions. Therefore an effort was made to help such engineers in the quick calculations of design live load moments (LLM) for small span skew RC bridges. For these bridges of practical dimension and skew angle as used by design engineers in Indian conditions are selected for the study. Two lane RC simply supported T-Beam bridges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In fact, it is a known fact that skew supports change the load path and loads transfer to the supports through their shortest path. A few researchers showed that the maximum bending moment in a girder in a skew bridge is smaller than its straight counterpart (Khaleel & Itani, 1990), and the shear in the girder at the obtuse corner is more significant when compared to those obtained in a non-skew (straight or right-angle) bridge of the same length and width (Menassa et al, 2007). Hence, an additional factor needs to be considered to adjust the load distribution factors of straight bridges when the engineer designs or evaluates a skew bridge.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is a known fact that skew supports change the load path and loads transfer to the supports through their shortest path. A few researchers showed that the maximum bending moment in a girder in a skew bridge is smaller than its straight counterpart (Khaleel & Itani, 1990), and the shear in the girder at the obtuse corner is more significant when compared to those obtained in a non-skew (straight or right-angle) bridge of the same length and width (Menassa et al, 2007). Hence, an additional factor needs to be considered to adjust the load distribution factors of straight bridges when the engineer designs or evaluates a skew bridge.…”
Section: Introductionmentioning
confidence: 99%
“…where R is the multiple presence factor; W is the width of lanes; and N g is the number of girders. Some investigations modified the GDF calculation methods of curved [3,14,15] and skewed [16,17] bridges based on AASHTO Standard specification and AASHTO LRFD specification. However, it was found that these methods overestimated the GDF and underestimated the stiffness of the bridge [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although Henry's method [18] is solely a function of the number of girders and the width of bridge roadway, it is widely used because it calculates highly conservative values for skewed bridges' LDFs [19]. The simplified models developed by Tarhini and Frederick [15] and Khaleel and Itani [20] yield accurate results only for single or two-lane loaded non-skewed bridges, while Menkulasi et al [21] proposed a set of equations to quantify LDFs for short-to medium-span composite precast inverted T-beam bridges that produce reasonably accurate results over the specified range of applicability.…”
Section: Introductionmentioning
confidence: 99%